Covalent Functionalizations of Poly(vinyl chloride) in Tune with Applications: An Update - Moulay, Saad (Journal of Research Updates in Polymer Science, 2015)
Poly(vinyl chloride), PVC, stands as one of the best polymer candidates as far as polymeric materials are strongly sought for in our today’s life. Functionalization of poly(vinyl chloride) (PVC) remains an appropriate way to fashion materials for specific applications. Molecules of different functionalities and sizes, up to macromolecules, were affixed to PVC matrix. Graft polymerization led to functionalized PVC with several properties for different applications. Some covalently modified PVCs, mainly with heteroatom-containing and cyclic molecules, proved to be biologically active and efficient scaffolds for enzyme/protein immobilization. Suitable functionalizations of PVC even ensured the effectiveness of the polymers as separative, ion-selective electrode, and fuel cell membranes. Some modifying agents incorporated in PVC made the polymeric materials convenient and reliable for solar cells design. Reactions of PVC with metal chelating molecules engendered PVC-metal complexes that were efficient polymer-supported catalysts for Heck, Sonogashira, and Suzuki-Miyaura coupling reactions. Heavy metal sorbents were also made by tailored functionalization of PVC. Modifications of PVC with allotropic carbon nanoparticles, including fullerene C60, carbon nanotubes, and graphene and their applications in the nanocomposites making are herein discussed. The newly emerged “click chemistry” and “living controlled radical polymerization, LCRP” were exploited in the functionalization of poly(vinyl chloride).